Going Local 2.0: How to Reform Development Agencies to Make Localized Aid More Than Talk - and Ang, Yuen Yuen (Stanford Social Innovation Review, 2018)
More and more global aid agencies believe they should replace one-size-fits-all best practices with locally tailored solutions, but they must shift from just agreeing to “go local” to preparing development experts for the task by taking on three major problems with their internal practices.